2021
DOI: 10.3390/genes12050620
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian and Yeast A49 and A34 Heterodimers: Homologous but Not the Same

Abstract: Ribosomal RNA synthesis is the rate-limiting step in ribosome biogenesis. In eukaryotes, RNA polymerase I (Pol I) is responsible for transcribing the ribosomal DNA genes that reside in the nucleolus. Aberrations in Pol I activity have been linked to the development of multiple cancers and other genetic diseases. Therefore, it is key that we understand the mechanisms of Pol I transcription. Recent studies have demonstrated that there are many differences between Pol I transcription in yeast and mammals. Our goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
2
3
0
Order By: Relevance
“…Therefore, the findings of the three studies support and supplement each other. We also show that functional cross-species complementation of RPA49/34 subcomplexes is possible, which is in line with a conserved role in supporting initiation and elongation stages of the transcription cycle while accumulating divergent regulatory properties (103,104,105). An increased flexibility of the clamp/stalk module in hPol I is indicated by the cryo-EM reconstruction (Fig 2 ) and may explain an increased rate of incorrect nucleotide addition we observe in comparison to the yeast enzymes in vitro (Fig 2B).…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, the findings of the three studies support and supplement each other. We also show that functional cross-species complementation of RPA49/34 subcomplexes is possible, which is in line with a conserved role in supporting initiation and elongation stages of the transcription cycle while accumulating divergent regulatory properties (103,104,105). An increased flexibility of the clamp/stalk module in hPol I is indicated by the cryo-EM reconstruction (Fig 2 ) and may explain an increased rate of incorrect nucleotide addition we observe in comparison to the yeast enzymes in vitro (Fig 2B).…”
Section: Discussionsupporting
confidence: 74%
“…We show that functional cross-species complementation of RPA49/34 subcomplexes is possible, which is in line with a conserved role in supporting initiation and elongation stages of the transcription cycle while accumulating divergent regulatory properties [92][93][94] . An increased flexibility of the clamp/stalk module in hPol I is indicated by the cryo-EM reconstruction (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…As previously mentioned, PAF49 and PAF53 act as a heterodimer and are required to support Pol I transcription and cell proliferation ( 36 , 41 , 42 , 61 , 67 ). Our study is the first to report that PAF49 is required to stabilize the levels of PAF53.…”
Section: Discussionmentioning
confidence: 99%
“…These results conflict with studies performed in yeast that report RPA34, the homolog to PAF49, is not essential for proliferation or rDNA transcription ( 31 , 32 , 48 , 49 ). Multiple studies from our laboratory and others have demonstrated that although there are similarities between the yeast and the mammalian Pol I systems ( 30 , 41 , 42 , 69 ), there are also many differences that warrant the need to study this system in mammals in order to effectively target the process of rDNA transcription in disease models where ribosome biogenesis and/or Pol I transcription is dysregulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation